2012
DOI: 10.1249/mss.0b013e3182442ecd
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eccentrically Biased versus Conventional Weight Training in Older Adults

Abstract: EB seems superior to CONV at increasing torque at high contraction velocities, whereas CONV seems more effective at improving some functional performance measures and vertical jump. This has important implications for preserving functional capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(113 citation statements)
references
References 34 publications
7
95
0
11
Order By: Relevance
“…The above studies 68,[70][71][72][73]75) observed an increase in pennation angle without an increase in fascicle length. In other words, studies which showed a lack of both fascicle length and pennation angle increases despite significant muscle hypertrophy are limited 76,77) . The two studies examined the fascicle arrangement before and after intervention for elderly individuals, implying that adaptation of the fascicle arrangement may be unlikely to occur in elderly people.…”
Section: Evidence Against Fascicle Length Changementioning
confidence: 99%
“…The above studies 68,[70][71][72][73]75) observed an increase in pennation angle without an increase in fascicle length. In other words, studies which showed a lack of both fascicle length and pennation angle increases despite significant muscle hypertrophy are limited 76,77) . The two studies examined the fascicle arrangement before and after intervention for elderly individuals, implying that adaptation of the fascicle arrangement may be unlikely to occur in elderly people.…”
Section: Evidence Against Fascicle Length Changementioning
confidence: 99%
“…Indivíduos idosos submetidos ao treinamento de força (TF) apresentam aumento significativo na força muscular [1][2][3][4] , potência muscular 5,6 , ativação muscular [7][8][9][10][11] e massa muscular 12,13 . A melhora na força muscular decorrente do treinamento de força nessa população aparenta ser semelhante [14][15][16] do que à observada em indivíduos jovens, o que lhe confere grande treinabilidade, apesar do prejuízo na função neuromuscular decorrente do envelhecimento 9 .…”
Section: Introductionunclassified
“…At 75 % 1RM, the eccentric phase was considerably under-loaded and thus, under-stimulated (1RM training loads are a limiting factor when used in eccentric exercise as they measure the load one can move concentrically only). Nevertheless, an earlier EBRE study supports these results [8]. Raj et al [8] randomized 13 community-dwelling subjects (68 ± 5 years) to EBRE two times per week for 16 weeks.…”
Section: Effects Of Eccentric Exercise On Muscular Strengthmentioning
confidence: 89%
“…While eccentric muscle action is a well-defined phenomenon in the literature [4], eccentric exercise modalities are varied and often ambiguously described. Current research on eccentric exercise in the older adult has described body weight [5,6], sub-maximal [7], maximal [8], and supra-maximal [9] concentric one-repetition maximum (1RM) loads with a wide range of eccentric phase tempos [7,10]. Some include [8] and others exclude [9] concentric muscle actions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation